Measurement of the B̄0 → D *+ℓ-ν̄ℓ decay rate and |Vcb| - Aubert, B; Barate, R; Boutigny, D; Couderc, F; Gaillard, J; Hicheur, A; Karyotakis, Y; Lees, J; Tisserand, V; Zghiche, A; Palano, A; Pompili, A; et al. (2005)
We present a measurement of the Cabibbo-Kobayashi-Maskawa matrix element |Vcb| based on a sample of about 53 700 B̄0 → D*+ℓ-ν̄ℓ decays observed by the BABAR detector. We obtain the branching fraction averaged over ℓ = e, μ, B(B̄0 → D*+ℓ -ν̄ℓ) = (4.90 ± 0.07(stat.) -0.35+0.36(syst.))%. We measure the differential decay rate as a function of w, the relativistic boost γ of the D*+ in the B̄0 rest frame. By extrapolating dΓ/dw to the kinematic limit w → 1, we extract the product of |V cb| and the axial form factor A1(w = 1). We combine this measurement with a lattice QCD calculation of A1(w = 1) to determine |Vcb) = (38.7 ± 0.3(stat.) ± 1.7(syst.) -1.3+1.5(theory)) × 10-3. © 2005 The American Physical Society.